The effects of periodically stagnant soil water conditions on biomass and methane yields of Silphiumperfoliatum. (May 2022) - Ruf, Thorsten; Emmerling, Christoph
Abstract: Resulting from the wide range of usages of bio-methane, anaerobic digestion has become a major issue. Beside biogenic residues, the cultivation of energy crops has significantly been expanded in Europe. Due to the increasing competition for land, sites with a low value for food production are predestined for cultivating feedstocks. Numerous studies have shown that perennial energy crops (PECs) present a valuable alternative to annual energy crops since they combine sound energy yields with substantial ecological advantages. Particularly under unprivileged sites conditions, PECs may fully leverage their strengths. Soils showing long lasting periods of soil moisture above field capacity (Stagnosols) were evaluated to be critical for silage maize cultivation as heavy harvest machinery may cause severe soil damages. Additionally, juvenile development of maize suffers from stagnant soil water. This study aimed to verify the results of a former pot experiment in which cup plant ( Silphium perfoliatum ) showed early sprouting, fast biomass development and higher yields under a soil water regime typical for Stagnosols. Thus, in the presented field experiment, silage maize and cup plant, were cultivated on well-drained soils (Cambisols) and on Stagnosols, and were compared concerning biomass and energy yields. On Stagnosols, the cup plant benefited likely from the higher soil water availability and produced average biomass yields of 14.3 t ha −1 a −1 being about 40% higher than on well-drained soils. The biochemical methane potential was 305 LN kg −1 VS and not affected by the soil type. Nonetheless, the methane yields per area of cup plant were still 35% lower than those of silage maize.